An interior inverse scattering problem in elasticity. Issue 3 (11th February 2022) - Ou, Yunhui; Zeng, Fang
ABSTRACT: We consider an interior inverse scattering problem of reconstructing the shape of an elastic cavity. We prove a reciprocity relation for the scattered elastic field and a uniqueness theorem for the inverse problem. Then we employ the decomposition method to determine the boundary of the cavity and present some convergence results. Numerical examples are provided to show the viability of the method.